Hope amidst crisis: exploring perinatal mental health and family dynamics in out-of-home care through virtual assessments during the UK COVID-19 response - Udita Iyengar; Jessica Heller-Bhatt; Jessica Heller-Bhatt (Frontiers Media S.A., 2024)
Caring for a young child exposed to early trauma, along with caregiving stress and heightened by the impact of lockdowns as a result of the COVID-19 response, may compromise the development of the parent-child relationship. Understanding a foster carer's attachment history and considering relational dynamics through an attachment lens may shed light on areas they need support in, to enhance their parenting capacity for vulnerable children. The feasibility of collecting and coding observational data and attachment interviews of foster carers and their children, when conducted remotely during COVID-19, needs to be explored. This perspective piece considers the impact on infant and perinatal health in the context of COVID-19 with particular emphasis on relational dynamics and attachment assessments, using a case study of a foster carer and her child in an out-of-home-care placement. Understanding these dynamics is crucial for safeguarding the well-being of both caregivers and vulnerable children during this challenging time.